TiO2-ZnPc nanoparticles functionalized with folic acid as a target photosensitizer for photodynamic therapy against glioblastoma cells - Gustavo Jardón-Guadarrama; Ma Elena Manríquez-Ramírez; Citlali E. Rodríguez-Pérez; Araceli Díaz-Ruiz; María de los Ángeles Martínez-Cárdenas; Alfonso Mata-Bermudez; Camilo Ríos; Emma Ortiz-Islas (Journal of Materials Science: Materials in Medicine)
Abstract The use of TiO2 as a photosensitizer in photodynamic therapy is limited due to TiO2 generates reactive oxygen species only under UV irradiation. The TiO2 surface has been modified with different functional groups to achieve activation at longer wavelengths (visible light). This work reports the synthesis, characterization, and biological toxicity assay of TiO2 nanoparticles functionalized with folic acid and combined with a zinc phthalocyanine to obtain a nano-photosensitizer for its application in photodynamic therapy for glioblastoma cancer treatment. The nano-photosensitizer was prepared using the sol-gel method. Folic acid and zinc phthalocyanine were added during the hydrolysis and condensation of titanium butoxide, which was the TiO2 precursor. The samples obtained were characterized by several microscopy and spectroscopy techniques. An in vitro toxicity test was performed using the MTT assay and the C6 cellular line. The results of the characterization showed that the structure of the nanoparticles corresponds mainly to the anatase phase. Successful functionalization with folic acid and an excellent combination with phthalocyanine was also achieved. Both folic acid-functionalized TiO2 and phthalocyanine-functionalized TiO2 had no cytotoxic effect on C6 cells (even at high concentrations) in comparison to Cis-Pt, which was very toxic to C6 cells. The materials behaved similarly to the control (untreated cells). The cell viability and light microscopy images suggest that both materials could be considered biocompatible and mildly phototoxic in these cells when activated by light. Graphical Abstract